Haematological toxicity in cancer cervix patients treated with concurrent chemoradiation by conventional technique- correlation with bone marrow radiation dose - Prachi Upadhyay; Pavan Kumar; Piyush Kumar; Ayush Garg; Arvind Kumar Chauhan (International Journal of Medical Research and Review, 2020)
Introduction: The standard of care for treatment of cancer cervix is concurrent chemoradiation followed by brachytherapy in the majority of cases. Conventional radiotherapy with chemotherapy causes haematological toxicities which may be related to radiation to pelvic bone marrow. The present study aims to study the haematological toxicities and correlate with the mean dose to the bone marrow.Material and Methods: Retrospective data of cancer patients treated in the institute in the year 2019 was retrieved. Haematological toxicities were analyzed in terms of CTCAE criteria. Mean dose to bone marrow was calculated after the delineation in the CT scan. The correlation between haematological toxicity and mean bone marrow was done using a paired t-test for statistical significance.Results: The data of 20 patients were retrieved. Anaemia Grade, I and Grade II-IV was seen in 65% and 35% respectively. Leukopenia Grade I and Grade II-IV were seen in 85% and 15% respectively and Lymphopenia Grade I and Grade II-Iv were seen in 55% and 45% respectively. The mean dose to bone marrow did not show any statistical significance with the severity of haematological toxicity. There was no Grade II-IV toxicity of neutropenia and thrombocytopenia.Conclusion: Conventional radiotherapy can safely be practice for patients with cancer cervix with acceptable haematological toxicities.